FOUR NEW SPECIES OF EPHOLCIS WATERHOUSE, 1875 (COLEOPTERA: SCARABAEIDAE: MELOLONTHINAE: MAECHIDIINI) FROM THE MOLUCCAS, INDONESIA - Raden Pramesa Narakusumo; Michael Balke (Research Center for Biology, 2019)
Here, we provide the first record of the chafer beetle genus Epholcis Waterhouse, 1875 from the Moluccan Islands, Indonesia. We describe four new species: E. acutus sp. nov., E. arcuatus sp. nov., E. cakalele sp. nov., and E. obiensis sp. nov. A lectotype is designated for Maechidius moluccanus Moser, 1920, which is redescribed and transferred to the genus Epholcis as E. moluccanus (Moser) comb. nov.